2020
DOI: 10.1111/jopr.13253
|View full text |Cite
|
Sign up to set email alerts
|

Is the Fixed Mandibular 3‐Implant Retained Prosthesis Safe and Predicable for Full‐Arch Mandibular Prostheses? A Systematic Review

Abstract: Purpose To evaluate implant and prosthetic survival rates of full‐arch rehabilitations retained by three implants in patients with edentulous mandibles. Materials and Methods This systematic review was developed following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. The focused question was: Are fixed mandibular 3‐implant retained prostheses safe and predicable for full‐arch mandibular prostheses? The Medline/PubMed and Cochrane Library databases were used to conduct the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The major disadvantage of fixed mandibular 3-implant retained prostheses is when one implant fails, the prosthesis is lost [ 20 ]. Bhering et al found decreased stress levels using this system on the bone, dental implants, screws, and abutments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major disadvantage of fixed mandibular 3-implant retained prostheses is when one implant fails, the prosthesis is lost [ 20 ]. Bhering et al found decreased stress levels using this system on the bone, dental implants, screws, and abutments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Brando TB et al systematic review, the survival rate for implants and prosthetics was 95.43 percent and 89.66 percent, respectively. Most prosthetic failures were associated with mobile implants, suggesting that when the “all-on-three” concept is applied, the prosthesis’ longevity is directly related to the implant’s ability to support the prosthesis [ 20 ]. In a research study conducted with an in vivo model, De Bryun H. and colleagues concluded that there is not much difference in axial force between three and four supporting implants.…”
Section: Introductionmentioning
confidence: 99%
“…To the author’s knowledge, there have been two previous systematic reviews conducted assessing outcomes with fixed mandibular prostheses supported by three implants [ 36 , 37 ]. The reviews concluded similar limitations, particularly the heterogeneity of the studies analysed and the lack of high-level evidence studies comparing two groups of three implants with larger numbers of implants.…”
Section: Discussionmentioning
confidence: 99%
“…A mean survival implant rate of 95.9% (95% CI: 94.6-97.3%) and a prosthetic survival rate of 97.0% (95% CI: 95.7-98.3%) were obtained after at least 1 year, up to 6 years. As far as the authors are aware, only one previous systematic review has focused solely on fixed mandibular prostheses supported by three implants [38], and it should be noted that the review did not include antagonist dentition or patient-reported outcomes. The results were similar to the present review in terms of implant survival rates (95.43%), although differences were found in prosthetic survival rates (89.68% versus 97%).…”
Section: Discussionmentioning
confidence: 99%